PENGARUH RASIO PROFITABILITAS, LEVERAGE DAN LIKUIDITAS TERHADAP EARNING GROWTH PADA PERUSAHAAN KESEHATAN PERIODE 2020-2022: PERTUMBUHAN LABA - Harris, Allan (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2024)
The company needs to analyze financial statements to obtain answers related to problems that may exist in the position of financial statements and results achieved in that period as well as for consideration in making future decisions at the company. Profit is one of the important things in showing the value of the company's performance. Earning growth itself has the understanding that a financial ratio shows the ability of a company to increase net income for the current year with the previous year. The purpose of this study is to determine the effect of financial ratios in which there are profitability ratios, leverage ratios and liquidity ratios to earnings growth in health companies who are members of the Sharia Securities List from 2020 to 2022. The sampling technique in this study used purposive sampling which obtained 45 total samples. This type of research uses quantitative methods using EVIEWS and Microsoft Office analysis tools. . The results of this study show that the profitability ratio has no influence on earning growth, while the leverage ratio has a negative influence on earning growth and for the liquidity ratio also has no influence on earning growth. However, simultaneously profitability, leverage and liquidity ratios have a positive and significant influence on earnings growth.